PLATELET FUNCTION IN TRAUMA: IS CURRENT TECHNOLOGY IN FUNCTION TESTING MISSING THE MARK IN INJURED PATIENTS?. Issue 1 (19th July 2022) - Schriner, Jacob B.; George, Mitchell J.; Cardenas, Jessica C.; Olson, Scott D.; Mankiewicz, Kimberly A.; Cox, Charles S.; Gill, Brijesh S.; Wade, Charles E.
ABSTRACT: Platelets are subcellular anucleate components of blood primarily responsible for initiating and maintaining hemostasis. After injury to a blood vessel, platelets can be activated via several pathways, resulting in changed shape, adherence to the injury site, aggregation to form a plug, degranulation to initiate activation in other nearby platelets, and acceleration of thrombin formation to convert fibrinogen to fibrin before contracting to strengthen the clot. Platelet function assays use agonists to induce and measure one or more of these processes to identify alterations in platelet function that increase the likelihood of bleeding or thrombotic events. In severe trauma, these assays have revealed that platelet dysfunction is strongly associated with poor clinical outcomes. However, to date, the mechanism(s) causing clinically significant platelet dysfunction remain poorly understood. We review the pros, cons, and evidence for use of many of the popular assays in trauma, discuss limitations of their use in this patient population, and present approaches that can be taken to develop improved functional assays capable of elucidating mechanisms of trauma-induced platelet dysfunction. Platelet dysfunction in trauma has been associated with need for transfusions and mortality; however, most of the current platelet function assays were not designed for evaluating trauma patients, and there are limited data regarding their use in this population. New or improved functional assays will help define the mechanisms by which platelet dysfunction occurs, as well as help optimize future treatment.